Pharyngeal collapsibility during sleep is elevated in insulin-resistant females with morbid obesity. Issue 6 (21st April 2016) - Llanos, Oscar L.; Galiatsatos, Panagis; Guzmán-Vélez, Edmarie; Patil, Susheel P.; Smith, Philip L.; Magnuson, Thomas; Schweitzer, Michael; Steele, Kimberley; Polotsky, Vsevolod Y.; Schwartz, Alan R.
Insulin resistance is associated with sleep apnoea, leading us to hypothesise that it is also associated with elevations in pharyngeal collapsibility, even in the absence of sleep apnoea. 90 bariatric patients were characterised for sleep apnoea, pharyngeal collapsibility and insulin resistance. Patients with a respiratory disturbance index (RDI) >10 events·h −1, diabetes mellitus, tonsillar hypertrophy and pulmonary disease were excluded. The remaining 14 females underwent collapsibility measurements (passive critical pressure, P critp ) during non-rapid eye movement sleep. The homeostasis model assessment (HOMA) index, a measure of insulin resistance, was derived from measurements of fasting glucose and insulin levels, and compared to P critp . Groups with high P critp compared to low P critp did not differ in age, body mass index or RDI. HOMA and insulin were elevated in the high P critp group compared to the low P critp group (p<0.02). P critp correlated with HOMA (Spearman's ρ=0.565, 95% CI 0.104–0.862; p=0.035) and insulin (Spearman's ρ=0.609 95% CI 0.196–0.835; p=0.021). Obese insulin-resistant subjects without frank diabetes or sleep apnoea demonstrate preclinical elevations in pharyngeal collapsibility, which may increase their susceptibility to sleep apnoea. Our findings suggest that insulin resistance could play a significant role in sleep apnoea pathogenesis by generating requisite elevations in pharyngeal collapsibility. Insulin resistance elevates pharyngeal collapsibility, thereby increasing susceptibility to sleep apnoea http://ow.ly/XZosr